Review for Costus specciosus (Koen.) Sm., Costaceae family. - Do, Thị Anh Thư (Tập san Khoa học và kỹ thuật trường Đại học Bình Dương, 2023)
Herbal medicines have played a critical role in the treatment and prevention of some diseases. Among a diversity of natural medicinal sources, Costus specciosus (Koen.) Sm. is an outstanding plant broadly distributed in tropical regions. C. specciosus has many biological activities, and it has been used in traditional medicine for treating various illnesses. This review article focuses to enhance and prepare a comprehensive review on phytochemical and pharmacological studies of C. specciosus, and aims to lay the foundation for further study on the extraction enhancement of these biomolecules and more useful formulations. Based on published scientific data, these plants may suggest a gigantic biological potential of an abundant source of chemical constituents and a variety of bioactivities contributing to therapeutic values.